The International Criminal Court: limits, potential and conditions for the promotion of justice and peace - Gegout, Catherine (Taylor & Francis, 2013)
The International Criminal Court (ICC) aims to promote not only justice, but also peace. It has been widely criticised for doing neither, yet it has to contend with some severe structural and political difficulties: it has limited resources, it faces institutional restrictions, it is manipulated by states, and it is criticised for an alleged selectivity in the way it dispenses justice. However, the icc could contribute significantly to the promotion of international justice and peace, and have a major impact on the prevention of crime, since its prosecutions represent a clear threat to highly placed individuals who commit serious crimes. While this article concentrates on the work of the icc in Africa, the only continent where it has issued indictments against suspected criminals, it also looks at its efforts on other continents. It argues that, in the larger international context, the contribution of the icc to international justice and peace depends on its institutional power and the support it receives from states, on its own impartial work, and on the way it is perceived by potential criminals and victims in the world.